Western Colonialism Over the Islamic World in the Middle East - Yanti, Silvia Rahma; Agustia, Dwi Putri; Amelia, Ulfi; Mubaraq, Zulfi; Kholil, Ahmad (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2024)
The study of Western Colonialism over the Islamic World in the Middle East is very important to be studied more deeply. This is because the study never stops being debated. The purpose of this paper is to understand 3 things: First, the Colonialism paradigm Second, internal and external factors that affect Colonialism Third, the positive and negative implications of Colonialism on the Islamic World in the Middle East. The method used is qualitative with a library research approachÂ  based on Muhammad Basri's theory, while data collection is by collecting, reading, understanding and analyzing books, articles and sources related to Western Colonialism and analyzed by content analysis techniquesÂ  3 things were found: First, the paradigm of Western Colonialism over the Islamic World in the Middle East has 3 forms: (1) Exploiting nature and dividing territory (2) Attacking (3) Domination of trade. Second, internally there are 2 factors that affect Colonialism: (1) Underdevelopment of knowledge (2) Internal division. As for externally, there are 3 factors that affect Western Colonialism: (1) Economic factors and European civilization (2) Crusades (3) Pursuit of power. Third, the positive implications of Colonialism on the Islamic World in the Middle East are 2 things: (1) The birth of a new group (2) Changes in social structure. Meanwhile, the negative implications are 3 things: (1) Taqlid thinking and Islamic backwardness (2) Divisions (3) The decline of local industries. The conclusion that this paper shows that the understanding of the history of colonialism is not only academic, but must also include community empowerment through active involvement and critical education.Keywords: Colonialism, Western (European), Middle East.